The Role of Volunteers in Improving Services in Elderly Integrated Service Centers - Edy Soesanto; Naufal Najib Abdurrahman (South East Asia Nursing Research, 2020)
The elderly attendance rate at the elderly integrated service centre for healthy sources of kangkung village is only 14.31%, this is far from the national coverage rate of 80%. The role of the volunteer is one of the factors supporting the presence of the elderly, through increasing the role of volunteer it is expected to be able to increase elderly visits. The Objective of this research to describe the role of the volunteer in the elderly integrated service centre in the village of kangkung. This research used descriptive research with cross-sectional approach. The study population was a cadre of healthy elderly integrated service centre sources kangkung village mranggen district. The research sample uses a total sampling technique. Data analysis in this study used univariate. As many as 12 people (60%) volunteer played a good role as coordinators, as many as 12 people (60%) played a good role as community mobilizers, as many as 10 people (50%) played a good role as providers of health promotion, as many as 15 people (75 %) played a good role in terms of basic aid providers, as many as 16 people (80%) played a good role in the documentation. The role of coordinator, community mobilizer, basic assistance provider and documentation has been going well, the role as health promotion provider is still poor. The volunteer is expected to be more active in playing roles in improving the services of elderly integrated service centre.